Research Progress on the Treatment of Premature Ovarian Failure Using Mesenchymal Stem Cells: A Literature Review - Wang, Jing; Liu, Wanru; Yu, Dehai; Yang, Zongxing; Li, Sijie; Sun, Xiguang (Frontiers in Cell and Developmental Biology, 2021)
Premature ovarian failure (POF) has become one of the main causes of infertility in women of childbearing age and the incidence of POF is increasing year by year, seriously affecting the physical and mental health of patients and increasing the economic burden on families and society as a whole. The etiology and pathogenesis of POF are complex and not very clear at present. Currently, hormone replacement therapy is mainly used to improve the symptoms of low estrogen, but cannot fundamentally solve the fertility problem. In recent years, stem cell (SC) transplantation has become one of the research hotspots in the treatment of POF. The results from animal experiments bring hope for the recovery of ovarian function and fertility in patients with POF. In this article, we searched the published literature between 2000 and 2020 from the PubMed database (https://pubmed.ncbi.nlm.nih.gov), and summarized the preclinical research data and possible therapeutic mechanism of mesenchymal stem cells (MSCs) in the treatment of POF. Our aim is to provide useful information for understanding POF and reference for follow-up research and treatment of POF.